1991
DOI: 10.1007/bf02265157
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase in intestine, liver and hepatic lesions of mummichog (Fundulus heteroclitus) from a creosote-contaminated environment

Abstract: Cytosolic glutathione S-transferase (GSH transferase) activity towards 1-chloro-2,4-dinitrobenzene (CDNB) was elevated approximately three to four-fold in intestine and liver of mummichog (Fundulus heteroclitus) collected from a creosote-contaminated site in the Elizabeth River, Virginia. Intestinal GSH transferase activity at the most heavily contaminated site, at a moderately contaminated site and at a relatively clean site averaged 3.64, 2.83 and 1.11µmoles/min/mg respectively, while values for liver at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Treatment of several fish species by intraperitoneal injection of PAHs produced a twofold induction of GST activity (George and Young 1988;Van Veld et al 1991). When rainbow trout were intraperitoneally injected with BNF, a twofold and 2.5-fold (Goksøyr et al 1987) induction of hepatic GST activity was found.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment of several fish species by intraperitoneal injection of PAHs produced a twofold induction of GST activity (George and Young 1988;Van Veld et al 1991). When rainbow trout were intraperitoneally injected with BNF, a twofold and 2.5-fold (Goksøyr et al 1987) induction of hepatic GST activity was found.…”
Section: Discussionmentioning
confidence: 96%
“…These alterations include suppression of enzymes involved in both xenobiotic activation and production of reactive oxygen species (e.g. CYP1A) and elevation of bene cial phase II detoxif ying enzymes such as G STs (van Veld et al 1991, Armknecht et al 1998). Overall, the pattern of expression of mummichog proteins and enzymes studied thus far (CYP1A, GST, Pgp) is similar to that believed to contribute to xenobiotic resistance in the early stages of carcinogen esis (Buchman et al 1985, Room i et al 1985, Fairchild et al 198 7, Farber 1991.…”
Section: Discussionmentioning
confidence: 98%
“…A correlation between GST activity and PAH burden has previously been reported in mussels (Gowland et al, 2002), and killifish collected in the PAH-contaminated Elizabeth River had elevated GST activity (Van Veld et al, 1991;Armknecht et al, 1998). Heavy metals or their metabolites are also inducers of hepatic GST as reported for arsenic-exposed rat hepatocytes (Liu et al, 2001).…”
Section: Hepatic Expression Of Xenobiotic-metabolizing Enzymes In Tarmentioning
confidence: 90%